2016
DOI: 10.3892/ijo.2016.3382
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 inhibitor, BIIB021, induces apoptosis and autophagy by regulating mTOR-Ulk1 pathway in imatinib-sensitive and -resistant chronic myeloid leukemia cells

Abstract: Development of drug resistance due to BCR-ABL point mutations and the persistence of leukemia initiating cells has become a major obstacle for tyrosine kinase inhibitors (TKIs) in the treatment of chronic myeloid leukemia (CML). The BCR-ABL protein is an important client protein of heat shock protein 90 (Hsp90). BIIB021, an orally available Hsp90 inhibitor, has activity against various cancer cells. However, little is known about the inhibitory effect of BIIB021 on CML cells. We evaluated the inhibitory effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 47 publications
3
31
1
1
Order By: Relevance
“…Specially, the mTOR/ULK1 signaling also generates autophagic protection in chronic myeloid leukemia cells, antagonizing the chemotherapeutic benefits of regular regimen [213]. However, contrary outcome has been obtained in breast cancer specimens, among which lower ULK1 expression indicates unfavorable prognosis and local development [214].…”
Section: Functions Of Ampk Signaling Components In Tumorigenesismentioning
confidence: 99%
“…Specially, the mTOR/ULK1 signaling also generates autophagic protection in chronic myeloid leukemia cells, antagonizing the chemotherapeutic benefits of regular regimen [213]. However, contrary outcome has been obtained in breast cancer specimens, among which lower ULK1 expression indicates unfavorable prognosis and local development [214].…”
Section: Functions Of Ampk Signaling Components In Tumorigenesismentioning
confidence: 99%
“…Meanwhile, BIIB021 causes cell death by regulating mTOR-Ulk1 signal pathway in chronic myeloid leukemia cells [23]. In the present study, BIIB021 synergized with triptolide in induction of death of thyroid carcinoma cells, and thus the influence of BIIB021 in combination with triptolide on these signal pathways in thyroid carcinoma cells was investigated.…”
Section: Synergistic Activity Of Biib021 With Triptolide Is Involved mentioning
confidence: 86%
“…Meanwhile, BIIB021 results in death of chronic myeloid leukemia cells through regulation of mTOR-Ulk1 signal pathway [23]. In regard to involvement of mTOR in cell survival, it was reported that the dual mTOR inhibitor MLN0128 inhibited tumor growth in Merkel cell carcinoma-xenograft model [29].…”
Section: Discussionmentioning
confidence: 99%
“…After 48 hours, collecting cells and stained with prewarmed (37 °C) MitoTracker® probe (100–500 nM) for 15–45 minutes. Immunoflorescent staining for cytochrome c was performed as described previously46. In details, cells were washed with PBS, and then fixed with 4% paraformaldehyde.…”
Section: Methodsmentioning
confidence: 99%